"En gift i blodet": Følelsesøkonomier i de dansk-grønlandske relationer - Thisted, Kirsten (K&K - Kultur og Klasse, 2018)
Inspired by Sara Ahmed, the article analyzes how long-established affective economies still dominate post-colonial relations between Danes and Greenlanders. Affective relationships between Greenlanders and Danes are embedded in historically inherited, asymmetric political, and financial power relations. While the political and economic conditions often are subject to analysis because data in these fields is relatively easy to access, it is much harder to access material that illuminates affective relationships. The article focuses on an email correspondence between two women, each of whom has a prominent place in the Danish-Greenlandic cultural debate. The two women know each other in advance and are both eager for the communication to succeed. It turns out not to be quite so simple. The analysis shows how the Dane, contrary to her own intentions, maintains the Greenlander in the role as the object of the Danish, evaluative and normative, gaze. The Greenlander protests against this and tries to renegotiate their positions so that the Greenlanders become subjects of their own actions and the history of Greenland. The article argues that it is not possible to understand the current political discussions, including debates on large scale projects, uranium extraction, and independence, unless these affects and their historicity are taken into account. A conversation about reconciliation must also begin here.